An Analysis of How Demographics Affect the Ethical Sensitivity of Accounting Students - Stichter, Roger L. (Christian Business Academy Review)
This paper reports the results of a test for determinants of ethical sensitivity in accounting students at public universities and Christian liberal arts universities. Society relies on the ethical practice of the accounting profession, and the recognition of ethical situations is a necessity for finding proper solutions. Results show none of the demographics tested as statistically significant determinants of ethical sensitivity. Such a study using religiosity as one of the independent variables had not previously been completed in the United States.